Coherent storage of photoexcited triplet states using 29Si nuclear spins in silicon. - Akhtar, W; Filidou, V; Sekiguchi, T; Kawakami, E; Itahashi, T; Vlasenko, L; Morton, J; Itoh, K (2012)
Pulsed electron paramagnetic resonance spectroscopy of the photoexcited, metastable triplet state of the oxygen-vacancy center in silicon reveals that the lifetime of the m(s)=±1 sublevels differs significantly from that of the m(s)=0 state. We exploit this significant difference in decay rates to the ground singlet state to achieve nearly ~100% electron-spin polarization within the triplet. We further demonstrate the transfer of a coherent state of the triplet electron spin to, and from, a hyperfine-coupled, nearest-neighbor (29)Si nuclear spin. We measure the coherence time of the (29)Si nuclear spin employed in this operation and find it to be unaffected by the presence of the triplet electron spin and equal to the bulk value measured by nuclear magnetic resonance.